Dose Response Study of a Novel Gold-Manganese Oxide Nano-Composite in an In Vivo Murine Model - Anupam Nath, Ramkrishna Pal, Leichombam Mohindro Singh, Himadri Saikia, Hasimur Rahaman, Sujit Kumar Ghosh, Ritwik Mazumder, Mahuya Sengupta (Journal of Applied Pharmaceutical Science, 2017)
In this study the multifunctional property of gold-manganese oxide nano-composites has been utilized to assess their prospect in living organisms. The nano-composite has been synthesized at a water/n-heptane interface under mild reflux conditions for desired functionalization. Nanomaterials have tremendous potential as biological response modifiers largely due to their novel properties in the quantum domain. However, it is imperative to have an improved understanding of the potential risks associated with exposure to nanomaterials as these can detrimentally affect the living system. Therefore, in our present study, we have performed few in vivo toxicity analyses in a murine model to determine their sub-lethal dose, so that subsequent applications can be effective but non-hazardous. Toxicity profiling is performed for the particle using parameters that include bio-accumulation assay by inductively coupled plasma atomic emission spectroscopy (ICP-AES), liver and kidney function assays by blood serum profiling, routine hematological study and histopathological analyses by hematoxylin and eosin (HE) staining. ICP-AES data reveal significant accumulation of metal in liver and kidney for doses 1.3x10-3 mg/kg body weight of mouse and higher. Hepatic function tests indicate atherosclerosis while renal function assays show significant abnormalities at such doses. From the hematological study, a clear indication of steatosis is observed at the above mentioned doses. The red blood corpuscle (RBC) count represents an IC50 value of 4.3x10-4 mg/kg body weight of mouse. From the present study, therefore, a sub-lethal dose lower than IC50 value can be used for future applications.
Keywords: Gold-manganese nanocomposite, in vivo toxicity, murine model, hematological and serum profiling, histopathology,bioaccumulation.